2002
DOI: 10.1017/s0033583501003754
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic apparatus of purple bacteria

Abstract: 1. Introduction 22. Structure of the bacterial PSU 52.1 Organization of the bacterial PSU 52.2 The crystal structure of the RC 92.3 The crystal structures of LH-II 112.4 Bacteriochlorophyll pairs in LH-II and the RC 132.5 Models of LH-I and the LH-I-RC complex 152.6 Model for the PSU 173. Excitation transfer in the PSU 183.1 Electronic excitations of BChls 22 3.1.1 Individual BChls 22 3.1.2 Rings of BChls 22 3.1.2.1 Exciton states 22 3.1.3 Effective Hamiltonian 24 3.1.4 Optical properties 25 3.1.5 The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
450
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 373 publications
(473 citation statements)
references
References 182 publications
18
450
0
5
Order By: Relevance
“…2 However, excitons within adjacent QD's are also able to interact through their resonant (Förster) energy transfer, 3 some evidence for which has been obtained experimentally in a range of systems. 4,5,6,7 As is shown below, this resonant transfer of energy gives rise to offdiagonal Hamiltonian matrix elements and therefore to a naturally entangling quantum evolution. It is proposed here that this interaction may be observed in a straightforward way through the observation of anticrossings induced in the coupled dot energy spectra by the application of an external static electric field.…”
Section: Introductionmentioning
confidence: 93%
“…2 However, excitons within adjacent QD's are also able to interact through their resonant (Förster) energy transfer, 3 some evidence for which has been obtained experimentally in a range of systems. 4,5,6,7 As is shown below, this resonant transfer of energy gives rise to offdiagonal Hamiltonian matrix elements and therefore to a naturally entangling quantum evolution. It is proposed here that this interaction may be observed in a straightforward way through the observation of anticrossings induced in the coupled dot energy spectra by the application of an external static electric field.…”
Section: Introductionmentioning
confidence: 93%
“…Such adaptation has been reported for the individual protein level; it is not as well understood at the system integration level. For instance, pigment networks of individual light harvesting proteins were reported to display optimality and robustness in their quantum yield with respect to the spatial organization of pigments and the site energy distribution Noy et al, 2006;Damjanovic et al, 2002); a similar robustness was reported with respect to size-scaling deformations of an entire vesicle (Sener et al, 2010). Prior studies did not take into account optimization of the complete energy conversion process, including ATP synthesis, the effects of vesicle composition influenced by growth conditions such as light intensity (Niederman, 2013;Woronowicz et al, 2013), the regulation of the redox state of the quinone/ quinol pool (Klamt et al, 2008), or the effects of cell-scale concentration and connectivity of chromatophores also influenced by light intensity at growth (Tucker et al, 2010).…”
Section: Optimality Of Vesicle Composition For Atp Productionmentioning
confidence: 99%
“…The functional principles displayed by the chromatophore and prevalent also in other photosynthetic systems include efficient excitonic coupling between components (Hu et al, 1997van Grondelle and Novoderezhkin, 2006b;Olaya-Castro et al, 2008;Sener et al, 2011), the utilization of quantum coherence (Ishizaki and Fleming, 2009a;Strümpfer et al, 2012), photoprotection by carotenoids (Damjanovic´et al, 1999), accommodation of thermal fluctuations, studied through experimental (Visscher et al, 1989;van Grondelle et al, 1994;Pullerits et al, 1994;Gobets et al, 2001;Janusonis et al, 2008;Freiberg et al, 2009) as well as theoretical (Damjanovic´et al, 2002;Ishizaki and Fleming, 2009b; van Grondelle eLife digest Photosynthesis, or the conversion of light energy into chemical energy, is a process that powers almost all life on Earth. Plants and certain bacteria share similar processes to perform photosynthesis, though the purple bacterium Rhodobacter sphaeroides uses a photosynthetic system that is much less complex than that in plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Energy that is absorbed by the B800 BChls or Cars is quickly transferred to the B850 exciton states which then transfer to exciton states of nearby LH2 and LH1 complexes. 14 With an accurate description of the excitation dynamics within the B850 ring and of the excitation transfer between B850 rings, insight into the function of an important component of the purple bacteria light harvesting system is gained.…”
Section: Introductionmentioning
confidence: 99%